West Java Province’s Paradiplomacy Practices in MSME Development toward Heilongjiang Province, China - Faykarulhaqq Ahsanu Nadiyya; Fuad Azmi (Journal of Paradiplomacy and City Networks, 2026)
This study aims to analyze the practice of economic paradiplomacy carried out by the West Java Provincial Government through its cooperation with Heilongjiang Province, China, in supporting the empowerment of Micro, Small, and Medium Enterprises (MSMEs). A descriptive qualitative approach was utilized, employing the theoretical frameworks of paradiplomacy and multilevel governance. The findings indicate that the West Java Government has played a strategic role as a subnational actor in international relations, particularly through the signing of a Memorandum of Understanding (MoU) and the implementation of business matching programs connecting MSMEs with Chinese business partners. This practice exemplifies the functional and adaptive engagement of local governments in international economic diplomacy and illustrates the concrete application of multilevel governance within Indonesia’s decentralization framework. The study concludes that economic paradiplomacy can serve as an effective instrument to support MSME internationalization and enhance regional economic development, while also fostering stronger bilateral ties, encouraging technology transfer, and opening broader opportunities for sustainable collaborative initiatives in the future. Furthermore, the West Java-Heilongjiang partnership highlights the potential for subnational cooperation to complement national diplomacy, positioning local governments as proactive agents of globalization capable of driving innovation, competitiveness, and inclusive growth for their respective regions.